Keir Hardie, the Bible, and Christian socialism : the miner's prophet - Smith-Christopher, Daniel L., autor (Scriptural traces : critical perspectives on the reception and influence of the Bible, 2024)
Daniel L. Smith-Christopher focuses on the life and efforts of Keir Hardie, one of the founders of the UK Labour Party and one of the foremost figureheads of trade unionism. Drawing upon the work of two contemporary and significant American theorists—Herbert Gutman’s classic essay on “Working-Class Religion” and Michael Gold's call for “Proletarian Literature”—Smith-Christopher marries British and American historical and theoretical debates to argue that Hardie's work is surely the quintessential example of a “proletarian exegesis” of the Bible. Beginning with a summary of the major events in Hardie's life, Smith-Christopher draws both upon existing biographies and more recent historical discussions that question assumption of British social history. He then reviews previous debates upon the influence of Hardie's own Christian faith upon his journalistic output, and assesses three Christian Socialists whose work was advertised and reviewed by Hardie himself: Dennis Hird, John Morrison Davidson, and Caroline Martyn. Smith-Christopher proceeds to Hardie's copious writings, both for The Labour Leader and separately published lectures, pamphlets, and somewhat longer works of autobiography and comment. Highlighting Hardie’s tendency to cite favorite texts (heavily from the Gospels and James, but also some notable Old Testament discussions), Smith-Christopher proves Hardie's serious discussion of these texts beyond mere political rhetoric; concluding by comparing a selection of Hardie’s favorite Biblical arguments with contemporary research in Biblical Studies about these same passages, evaluating the problems and possibilities of proposing a “Proletarian Exegesis”.